DESIGN OF DUAL BAND MONOPOLE ANTENNA FOR BLUETOOTH AND ULTRA WIDE BAND WITH TRIPLE NOTCH USING ELECTROMAGNETIC BANDGAP STRUCTURE (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
This paper focuses on the applications of dual band antenna for Bluetooth (2.4 - 2.484 GHz) and ultra-wideband (3.1 - 10.6 GHz) with triple notch band. A spanner shape with a rectangular strip monopole and the partial rectangular ground plane is used as the desired dual band antenna. The electromagnetic bandgap EBG structures are placed near the feed line to obtain notch frequencies at 3.5 GHz, 5.5 GHz, and 7.5 GHz. The detailed parametric study of the antenna is presented and discussed. The input impedance and current distributions are used for the effects of EBG and narrow strips. Test results of the fabricated design show a good similarity with simulated outcomes, validating design principles. The designed antenna exhibits nearly omnidirectional radiation patterns, stable gain, appreciable efficiency, linear phase, and constant group delay over the desired bands. Hence the proposed antenna is expected to be suitable for both Bluetooth and UWB applications.
Keywords: Bluetooth; Ultra wide band; Electromagnetic band gap; Worldwide interoperability for microwave access; Wireless local area network; X-band; Bande interdite électromagnétique